Decision Making in Adopting Cultural Changes during the Covid-19 Pandemic - Tajuddin, Fatjri Nur; Sabila, Andi Amalia; Nisa, Andi Khaerun; A Rahman, Fatmawati (Jurnal Pendidikan Ilmu Sosial, 2022)
Cultural changes that occur in global society are currently taking place rapidly along with the emergence of the covid-19 virus. These changes can inluence the socio-cultural life of the community due to the fact that they have to adapt to new habits. This study examined how the strategy is in determining decision making on cultural changes that are affected by the covid-19 pandemic. Using qualitative research methods through participatory observation and interviews in Langkura Village, Jeneponto Regency, this research was analyzed based on the process of socio-cultural change that was affected by the COVID-19 pandemic in making decisions about these changes. In addition, it relates the phenomenon to past situation by using various literature sources with the similarity of the condition of the community with a farmer background. This research is very important in analyzing policy making by the authorities in seeing the rapid socio-cultural changes to the survival of the farmers. In the end, it showed that the Langkura people are very considerate in making decisions despite the many social pressures, but even so, they actually need the development of their group development.